Openness to trade and deforestation at the Brazilian Amazon: a spatial econometric analysis - Weslem Faria; Alexandre Almeida (European Regional Science Association (ERSA), 2011)
The Brazilian Amazon is a large piece of land that hosts only 12% of Brazilian population. Even this low figure and people mostly living in urban areas, the overexploitation of the forest resources driven by economic activities seems to be out-of-control. In the 1970s, abundant government subsidies/incentives for mining, crop and beef production, and gigantic road projects provided infra-structure to the new settlers coming from other parts of the country. For the last decades, frontier regions of Amazon have been a major scene of land conflicts between farmers, squatters, miners, indigenous group and public authorities. Furthermore, from the openness of economy in the 1990s, we also find some evidence that the very attractive demand of international markets for timber, and recently, the attractive international prices of agricultural commodities are determinants that have been also pushing to more deforestation through the conversion of forest to new agricultural areas. The main objective of this paper is to investigate how international trade has affected the dynamics of deforestation in the Brazilian Amazon. The analysis also focuses on the expansion of crop and cattle activities, and other determinants such as gross domestic product, demographic density and roads. To achieve such goal, we combine standard econometrics with the spatial econometrics in order to capture, across the space, the socio-economic interactions among the agents in their interrelated economic system. The data used in this study correspond to a balanced panel for 732 counties from 2000 to 2007 totalizing 6,256 observations. The main findings suggest that the openness to trade indicator used–export plus import over GDP–goes up, the result is more deforestation. We also find that beef cattle and the production of soybeans, sugarcane and cotton are pushing to more deforestation in the region. The extraction of firewood and timber had both a positive and significant in impact on deforestation, as expected. Moreover, as the GDP goes up, it pushes to more deforestation as well. On the other hand, as the square of GDP goes up indicate less deforestation, supporting, to some extent, the environmental Kuznets Curve hypothesis.
Keywords: 330